Solve for y -2.4=3y

Math
-2.4=3y
Rewrite the equation as 3y=-2.4.
3y=-2.4
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3y=-2.4 by 3.
3y3=-2.43
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3y3=-2.43
Divide y by 1.
y=-2.43
y=-2.43
Divide -2.4 by 3.
y=-0.8
y=-0.8
Solve for y -2.4=3y

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top